Digital Media Marketing Communication at Jakarta National Monument Attractions - Murhadi; Nathaniel; Nenny Wahyuni (The Postgraduate School of Tourism Sahid Polytechnic, 2024)
Purpose: This study aims to (a) find digital marketing communication in Monas and (b) determine the number of tourist visits and activities at Monas attractions. Research Metods: This research uses a qualitative method approach; data is obtained through documentation, interview, and observation techniques, and then the research data is analyzed through data reduction, data presentation, and conclusion drawing digital marketing communication activities for branding and promotion activities or attractions in the Monas Jakarta Area. Result and discussion: The results showed digital marketing communication through social media platforms and websites like TikTok, Instagram, and YouTube. This strategy effectively increases tourist visits and activities where the National Monument always makes preparations according to visitors' needs. The efforts made by Monas Jakarta Management to increase attractiveness can be seen by improving services, organizing events at Monas, and conducting promotional activities through social media. Implication: This research concludes that digital marketing communication carried out by the Jakarta Monas Management is well implemented, as can be seen from the number of visitors, which has increased every year after the COVID-19 pandemic. This study recommends that promotion through social media be carried out more intensely to attract more visitors. Keywords: Communication, Digital Marketing, Monas, Branding, Promotion, Visitability Level.